Umiejętności zawodowe księgowych w wojskowych jednostkach budżetowych - Cybulska, Marta (The Professional Skills of Accountants of the Military Budgetary Units, 2005)
The growing expectations of employers, customers and societies are related to the professional and social figures accountants. These expectations among other things are the result of the increase in receipt information, the quick rate loss of timeliness assimilative information and scientific as well as technological development, which caused that shaping and developing professional skills of accountants have to be done on the high level. The research was carried out among accountants working in the military budgetary units subordinate to the 3rd air defense corps. The research consisted in filling postal questionnaire (in February 2005). The questionnaire contained 32 questions (29 close questions and 3 open questions) which referred to personal information, education, professional carrier, possessed skills, usefulness skills for accountants, need to perfect and develop skills. Questioned accountants were of different age, sex, and professional experience. So the collected material cannot be representative for all accountants in Poland but can be very precious and important source of information.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1079, s. 170-181